Early response of Nothofagus antarctica forests to thinning intensity in northern Patagonia - Goldenberg, Matías Guillermo; Nacif, Marcos Ezequiel; Oddi, Facundo José; Garibaldi, Lucas Alejandro (Canadian Journal of Forest Research)
Nothofagus antarctica (G. Forst.) Oerst. stands of northern Patagonia (Argentina) have great potential to provide multiple ecosystem services. Nonetheless, the lack of basic information limits the application of silvicultural treatments to this forest type. This study reports the early response to three systematic strip thinning treatments (30%, 50%, and 70%) carried out during 2013 in a 30-year-old N. antarctica stand, where control plots (i.e., no thinning) were also established. Subplots were located within each plot. Basal diameters (BD) of all retained stems were measured in the non-vegetative season (winter) of 2016, 2017, and 2018 to calculate basal diameter annual increment (BDI) and stand volume growth. BDI ranged from 1.9 mm·year-1 in the control plots to 2.7 mm·year-1 at 70% thinning. Relative BDI also responded positively to thinning intensity. Stand volume growth decreased non-linearly with thinning intensity from 3.36 m3·ha-1·year-1 in the control plots to 0.71 m3·ha-1·year-1 when thinning was 70%. Smaller differences were observed between control plots, 30% thinning, and 50% thinning. Our results show that N. antarctica forests, in the stem exclusion stage, respond to strip thinning. Thus, silviculture based on this management system could favor the development of retained trees without losing productivity if it remains under 50% intensity. This outcome represents an important incremental contribution to the design of silvicultural interventions in northern Patagonia. Fil: Goldenberg, Matías Guillermo. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Conicet - Patagonia Norte. Instituto de Investigaciones En Recursos Naturales, Agroecologia y Desarrollo Rural. - Universidad Nacional de Rio Negro. Instituto de Investigaciones En Recursos Naturales, Agroecologia y Desarrollo Rural.; Argentina Fil: Nacif, Marcos Ezequiel. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Conicet - Patagonia Norte. Instituto de ...